Lost in Administration: (Re)Producing Precarious Citizenship for Young University-Educated Intra-EU Migrants in Brussels. (June 2018) - Simola , Anna
The mounting backlash against intra-EU migration in various EU countries has triggered national policies seeking to restrict EU citizens' social rights and freedom of movement. Building on and expanding Noora Lori's work around this concept, the article examines intra-EU migrants' increasingly unsettled legal statuses as potentially precarious citizenship . Focusing on the experiences of young university-educated intra-EU migrants in Brussels, the article claims that, in the absence of straightforward EU legislation and explicit government policies, administrative actors use their discretion to draw indeterminate boundaries enforcing conditionality and temporariness of status for EU citizens in precarious work arrangements, therefore often increasing the pressure on them to take further precarious jobs. The article argues that, under the conditions of precarious employment, not even migrants with privileged access to citizenship rights are protected from processes of boundary enforcement that institutionalise the ambiguity of statuses and produce precarious citizenship.